Public Swearing In Ceremony for Judges Charles Hamlin, Gene Gomes, Ralph Nunez, Mario Olmos and Victor Papadakis at Veterans' Memorial Auditorium - Watkins, Howard::::::::: (1983)
Superior Court Presiding Judge Frank Creede, Jr. administering oath to Gene Gomes, Ralph Nunez and Mario Olmos; to right: Judges James Ardaiz, Victor Papadakis, John "Nip" Gallagher, Buck Levis and Steven Vartabedian